A digital health peri-operative cognitive-behavioral intervention to prevent transition from acute to chronic postsurgical pain in adolescents undergoing spinal fusion (SurgeryPalTM): Study protocol for a multisite randomized controlled trial. - Rabbitts, Jennifer A.; Zhou, Chuan; De la Vega, Rocío; Aalfs, Homer; Murray, Caitlin B.; Palermo, Tonya M. (BMC, 2021)
Background: Spinal fusion surgery is associated with severe acute postsurgical pain and high rates of chronic postsurgical pain in adolescents. Psychological distress, sleep disturbance, and low pain self-efficacy predict higher acute pain and likelihood of developing chronic postsurgical pain. Interventions targeting baseline psychosocial risk factors have potential to interrupt a negative trajectory of continued pain and poor health-related quality of life (HRQL) over time but have not yet been developed and evaluated. This randomized controlled trial will test effectiveness of a digital peri-operative cognitive-behavioral intervention (SurgeryPalTM) vs. education-control delivered to adolescents and their parents to improve acute and chronic pain and health outcomes in adolescents undergoing spine surgery. Methods: Adolescents 12–18 years of age undergoing spinal fusion for idiopathic conditions, and their parent, will be recruited from pediatric centers across the USA, for a target complete sample of 400 dyads. Adolescents will be randomized into 4 study arms using a factorial design to SurgeryPalTM or education control during 2 phases of treatment: (1) pre-operative phase (one-month before surgery) and (2) post-operative phase (1 month after surgery). Acute pain severity and interference (primary acute outcomes) and opioid use will be assessed daily for 14 days following hospital discharge. Chronic pain severity and interference (primary acute outcomes), as well as HRQL, parent and adolescent distress, sleep quality, and opioid use/misuse (secondary outcomes), will be assessed at 3 months and 6 months post-surgery. Discussion: Demonstration of effectiveness and understanding optimal timing of perioperative intervention will enable implementation of this scalable psychosocial intervention into perioperative care. Ultimately, the goal is to improve pain outcomes and reduce reliance on opioids in adolescents after spine surgery.
Keywords: Dolor en niños; Escoliosis - Tratamiento; Adolescent scoliosis; Acute pain; Chronic pain; Psychosocial intervention; mHealth; Randomized controlled trial